2022
DOI: 10.1155/2022/5794350
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products for Cancer Therapy: A Review of Their Mechanism of Actions and Toxicity in the Past Decade

Abstract: The ethnopharmacological information gathered over many centuries and the presence of diverse metabolites have made the medicinal plants as the prime source of drugs. Despite the positive attributes of natural products, there are many questions pertaining to their mechanism of actions and molecular targets that impede their development as therapeutic agents. One of the major challenges in cancer research is the toxicity exerted by investigational agents towards the host. An understanding of their molecular tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 144 publications
0
21
0
Order By: Relevance
“…Acting as natural modifiers of biochemical reactions, herbal medicines are promising adjunctive therapeutics. The healing properties of medicinal plants are due to a wide range of pharmacologically active ingredients: alkaloids, glycosides, saponins, and other compounds [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acting as natural modifiers of biochemical reactions, herbal medicines are promising adjunctive therapeutics. The healing properties of medicinal plants are due to a wide range of pharmacologically active ingredients: alkaloids, glycosides, saponins, and other compounds [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent scientific studies have shown that many food plants, medicinal plants and spices contain bioactive components such as piperine, curcumin, thymoquinone, crocin, capsaicin, polysaccharides, polyphenols, and other bioactive metabolites, which have been shown to have anticancer, anti-Inflammatory, antioxidant and immunomodulatory effects [9][10][11]. In addition.several studies reported that many natural polyphenols, which have antioxidant, anti-inflammatory and anti-diabetic properties, have beneficial effects against protein aggregates found in AD.…”
Section: Introductionmentioning
confidence: 99%
“…The regular consumption of adequate amounts of fruit and vegetables may reduce the incidence of cancer, and this evidence raised interest in the therapeutic use of these foods as natural sources of anticancer agents. This possibility has triggered the attention of researchers, and currently a huge body of evidence supports the anticancer action of naturally occurring compounds [ 31 , 32 ]. Being a rich source of health beneficial nutrients (carbohydrates, vitamins, minerals, fibers, etc.)…”
Section: Discussionmentioning
confidence: 99%